SISTEM PAKAR PENYAKIT GINJAL PADA MANUSIA MENGGUNAKAN METODE FORWARD CHAINING - Samsilul Azhar; Herlina Latipa Sari; Leni Natalia Zulita (Jurnal Media Infotama, 2014)
Selection of issues regarding the kind of kidney disease as a sample of this study, is the fact that diseases Kidney is an important organ in our body's metabolic system, because the density of activity, we often forget to take care of. Irregular diet, inadequate intake of fiber and mineral water, as well as the consumption of food or drink high calorie instant, un-wittingly aggravate the kidneys. Starting from the filtration, reabsorption, to augmentation of nutrients that under to the kidneys via the blood. The purpose of this research is to build an expert system Kidney disease using Visual Basic 6.0 programming language that is capable of providing services to the public and delivery of information related to kidney disease. Pre-study and research conducted at the Hospital Dr. M.Yunus Bengkulu which began in March to August 2014. In this research, data collection is done by using the method of observation, interviews, and literature. From the results of this study indicate that the presence of kidney disease diagnosis expert system in humans can provide significant benefits, among others, the processing of data and consultation process carried out quickly and produce a fairly accurate report, thus making the job more effectively and efficiently.Keywords: Expert System, Disease, Kidney, Human